Developing a Research Skill Set - You, Y. Nancy; Bednarski, Brian (Clinics in Colon and Rectal Surgery, 2014)
The recent decades have witnessed a significant expansion in the diversity of career paths within academic surgery. Although the skills for providing exemplary surgical care and for maintaining a strong work ethic are the foundations of an academic surgeon, deliberate career planning and organized acquisition of research skills contribute to the success of an academic career. In this article, we identify a set of core academic skills and propose a framework for acquiring them. We also describe specific career paths within academic surgery and provide an overview of the opportunities for acquiring specific skill sets. The development of an academic career is challenging, and firm knowledge of the personal motivations will sustain and endure the time needed for acquiring the needed skills.
Keywords: academic surgery; research skills; clinical trials; health outcomes; surgical education